Encouraging the return to museums through the through enriching of the experience and the feeling of pride - Blanco, T.; Loureiro, S. M. C. (13th Annual Conference of the EuroMed Academy of Business: Business theory and practice across industries and markets, 2020)
The aim of the current study is to investigate the effect of museum experiences on visitors' willingness to recommend a museum and desire to return, based on the influence of the perception of coolness and the feeling of authentic pride. A sample of 308 usable questionnaires retrieved from four Lisbon (Portugal) museums provide a good understanding of the drivers of revisit and recommend intentions. Museum Atmospheric Cues contribute to the perception of Museum Coolness and the feeling of Authentic Pride, which, in turn, have an effect on the intentions to Recommend and Revisit a museum. The perception of Museum Coolness has a stronger influence on both intentions to Revisit and Recommend.